THE EFFECT OF POST INGESTIVE FEED BACK OF NUTRIENTS ON INTAKE OF OVEN-DRIED GLIRICIDIA LEAVES - KARDA, I W. (Majalah Ilmiah Peternakan, 2012)
ABSTRACT Two trials were conducted to assess the effect of post-ingestive feed back of nutrients on intake of gliricidia leaves by sheep. In trial 1, six rumen fistulated sheep were used to compare four dietary treatments in a randomised complete block design. Gliricidia leaves were fed ad lib. with no other additives (treatment 1) or with 15 mg metoclopramide/kg body weight (treatment 2), or 0.5 % body weight of ground barley grain (treatment 3), or 0.5% body weight of cottonseed meal (treatment 4) administered into the rumen within 30 minutes before feeding the leaf. In trial 2, the same sheep as in trial 1 were used to compare four dietary treatments in a randomised complete block design. Gliricidia leaves were fed ad lib. (treatment 1), or with 0.5% body weight of cottonseed meal either administered into the rumen before feeding the leaf (treatment 2), or mixed with the leaf (treatment 3), or fed separately prior to offering the leaf (treatment 4). The results showed that administration of cottonseed meal into the rumen in trial 1 increased significantly daily intake of gliricidia leaves compared to the control treatment, or to administration of metoclopramide into the rumen (285 g vs. 171 g vs. 142 g) dry matter. However, administration of ground barley grain into the rumen did not significantly differ from any other treatment. In addition, none of dietary manipulations in trial 2 increased intake of gliricidia leaves by the sheep.